2010
DOI: 10.1001/archoto.2010.42
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Fat Injection Laryngoplasty in Unilateral Vocal Cord Paralysis

Abstract: Fat injection laryngoplasty seems to be effective in enhancing acoustic and quality of life outcomes in patients with unilateral vocal cord paralysis. The effect is sustainable over 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 19 publications
5
39
0
1
Order By: Relevance
“…The improvement in voice quality parameters observed in this study is consistent with those in previous studies . For instance, a study on 33 patients with UVCP in Taiwan observed that jitter had improved from 2.7 at baseline to 1.3 at month 3, which is comparable with our observed effect size. Hartl and colleagues also observed that acoustic parameters (eg, jitter and shimmer) reduced quickly after one month of surgery and maintained up to 24 months .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The improvement in voice quality parameters observed in this study is consistent with those in previous studies . For instance, a study on 33 patients with UVCP in Taiwan observed that jitter had improved from 2.7 at baseline to 1.3 at month 3, which is comparable with our observed effect size. Hartl and colleagues also observed that acoustic parameters (eg, jitter and shimmer) reduced quickly after one month of surgery and maintained up to 24 months .…”
Section: Discussionsupporting
confidence: 92%
“…Hartl and colleagues also observed that acoustic parameters (eg, jitter and shimmer) reduced quickly after one month of surgery and maintained up to 24 months . Moreover, the index of vocal ageing (ie, harmonics‐to‐noise ratio) in our study was improved by almost 57% at months 1‐3 which was also observed by a previous study . We also found substantial improvement in glottal patency, glottal gap, vocal cord and voice handicap index.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The literature indicates that hyaluronic acid injected into Reinke’s space has the ability to stimulate growth of new connective tissue – collagen, fibroblasts, and hyaluronic acid – providing long-term filling and elasticity of the vocal fold [13]. In comparison to other implantable materials such as autologous fat, Teflon, collagen, or calcium hydroxylapatite, hyaluronic acid seems to be quite resistant to resorption [2,14,15]. As reported by other authors, resorption of hyaluronic acid takes about 6–12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Die Injektion von Eigenfett ist seit mehr als 20 Jahren in der Hals-Nasen-Ohrenheilkunde etabliert. Regelmäßig werden Stimmlippenaugmentationen [1,2] sowie Lipoinjektionen bei Narben und Konturdefiziten durchgeführt [3,4]. Das entnommene Fettgewebe enthält interessanterweise relevante Mengen an adipogenen Stammzellen [5,6], welchen wundheilungsfördernde Eigenschaften zugeschrieben werden [7].…”
Section: Hintergrund Von Lipoinjektionen In Der Otorhinolaryngologieunclassified